Efektifitas relaksasi aromaterapi terhadap kualitas tidur lansia: Literature review - Mayda Asmarani; Suri Salmiyati; Agustina Rahmawati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Insomnia in the elderly was recognized as a common health problem associated with aging, often leading to decreased well-being and quality of life. This study aimed to analyze the effectiveness of aromatherapy relaxation in improving sleep quality among the elderly through a review of published research. A literature review was conducted using Science Direct, PubMed, Wiley Library, and Google Scholar. Articles published between November 2018 and November 2023 were screened using the PRISMA method with inclusion criteria of accessible full texts from both national and international journals. Quality appraisal was performed with the JBI Critical Appraisal tool. Four quasi-experimental studies met the criteria and were analyzed. The findings indicated that aromatherapy, particularly with lavender and jasmine oils, was effective in reducing insomnia symptoms and enhancing sleep quality in elderly populations. The intervention was found to be safe, simple, and affordable as a non-pharmacological option. It was concluded that aromatherapy could serve as an effective complementary therapy to support elderly health, while healthcare providers were encouraged to promote its use and future studies were recommended to explore additional influencing factors.